Come in uno specchio: Dittico francescano (con piccola predella) - Ballarini, Marco (La Scuola Cattolica, 2025)
In the Twentieth Century the figure of St. Francis was point of reference for the most disparate sensibilities and currents of thought which have thus produced texts of very different “fidelity”, as well as for different literary value. The universality of the Saint of Assisi, with the consequent ability to propose itself as a “mirror” in which are reflected the aspirations of the individual or of the particular historical moment, is confirmed by the analysis of three recent contributions: Dario Fo with Lu santo jullàre Françesco draws to himself the Holy on the stage, with continuous trade between actor and character; Alda Merini (Francesco. Canto di una creatura) finds in him the neutral lover, inventor of a new language, capable of sound again his past experience; Milvia Bollati, finally (Frate Francesco) tells the story of the important episodes of franciscan legend, leaving that the heart is continually called forth by the one who seems to be ideal and refuge.